Development of a novel direct compressible co-processed excipient and its application for formulation of Mirtazapine orally disintegrating tablets - Loke, Ying Hui; Chew, Yik-Ling; Ashok Kumar, Janakiraman; Lee, Siew-Keah; A.B.M. Helal, Uddin; Goh, Fu Choon; Kee, Phei Er; Ng, Hui Suan; Long, Chiau Ming *; Liew, Kai Bin (Taylor and Francis Group, 2024)
Introduction Orally disintegrating tablets (ODTs) are designed to dissolve in the oral cavity within 3 min, providing a convenient option for patients as they can be taken without water. Direct compression is the most common method used for ODTs formulations. However, the availability of single composite excipients with desirable characteristics such as good compressibility, fast disintegration, and a good mouthfeel suitable for direct compression is limited.